Bacterial Causes and their Antimicrobial Susceptibility Testing among Urinary Tract Infection Patients in Tobruk Area, Libya - Mostafa, Mohammed T.; Mustafa , Khalid S.; Kumar, Brijesh (Al-Mukhtar Journal of Sciences, 2021)
Urinary tract infections are very common among people of all ages, but the disease is more prevalent in women, so proper clinical and laboratory diagnosis, and the right treatment are very important to avoid complications and antimicrobial resistance. This study aimed to determine the bacterial causes and antibiotic susceptibility patterns of UTI patients. Recorded results of 6065 urine sample cultures and their antimicrobial susceptibility tests from the Department of Microbiology in Tobruk Medical Center, Tobruk City, were obtained from September 2016 to December 2018. The data was analyzed and discussed in compare with other studies. The study showed that a UTI is more common in females (78.8%) compared with male patients (21.2%). Gram-negative bacteria accounted for the majority of urinary pathogens (90%), where E. coli alone was (58.4%), klebsiellae (17.4%), Proteus (10.7%), while Pseudomonas species was the least common (3.3%) of the total. While the Gram-positive bacteria S. aureus constituted 9.6% of the total. The study was found statistically significant (P=0.000). The most effective antibiotics against all uropathogens were Imipenem and Amikacin, and less effective antibiotics were Ampicillin and Amoxicillin-clavulanic acid. This study concluded that the most common cause of UTI in Tobruk was Escherichia coli and the most effective antibiotics appear to be Imipenem and Amikacin.